2019
DOI: 10.3390/ijerph16091517
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miRNAs in Zearalenone-Promotion of TM3 Cell Proliferation

Abstract: Zearalenone (ZEA) is a non-steroidal estrogen mycotoxin produced by several Gibberella and Fusarium species. Accumulating evidence has indicated that ZEA strongly stimulates cell proliferation. However the detailed molecular and cellular mechanisms of ZEA-mediated induction of cell proliferation have not yet been completely explained. The aim of this study was to detect the role of miRNAs in ZEA-mediated induction of cell proliferation. The effects of ZEA on cell proliferation were assessed using a cell counti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Similar results on Leydig cells were found by Wang et al [ 101 ], with ZEA 50 μM. By contrast, Zheng et al [ 89 ], found that low doses of zearalenone (0.01, 0.02, 0.03, 0.04, and 0.05 μmol/L) stimulated cell viability of TM3 cells (Leydig cells) measured by using the xCELLigence real-time cell analysis. Also, under the action of ZEA (20μM), cell viability of Sertoli cells derived from Male Wistar, which are important for male reproductive system, increased over control [ 102 ].…”
Section: Effect Of Zearalenone On Adaptive Immune Responsesupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results on Leydig cells were found by Wang et al [ 101 ], with ZEA 50 μM. By contrast, Zheng et al [ 89 ], found that low doses of zearalenone (0.01, 0.02, 0.03, 0.04, and 0.05 μmol/L) stimulated cell viability of TM3 cells (Leydig cells) measured by using the xCELLigence real-time cell analysis. Also, under the action of ZEA (20μM), cell viability of Sertoli cells derived from Male Wistar, which are important for male reproductive system, increased over control [ 102 ].…”
Section: Effect Of Zearalenone On Adaptive Immune Responsesupporting
confidence: 80%
“…The study of Zhang et al [ 88 ] demonstrated that ZEA at 10–50 μg/mL had a time and dose dependent inhibitory action on mouse thymic epithelial cells proliferation and arrested thymic cells in G2/M phase of cellular cycle. Studies performed on TM3 cells shows that low doses of ZEA increases cell proliferation [ 89 ].…”
Section: Effect Of Zearalenone On Adaptive Immune Responsementioning
confidence: 99%
“…The finding in terms of proliferation reported here may be due to the expression of two ER (α-ER and β-ER), which has also been reported for other xenoestrogens acting on liver cancer cells [ 42 ]; however, signaling pathways are not yet fully established. It is plausible that micro-RNAs are also involved in stimulating cell proliferation by silencing various cell cycle inhibitors; accordingly, it has been stated that ZEN induces oxidative stress, which may be a regulator of miRNAs, interfering with micro-RNA expression [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The toxicodynamic effects of ZEA, a mycotoxin produced by Fusarium species, involve complex molecular interactions, and emerging research has highlighted the role of regulatory miRNAs in orchestrating the cellular response to ZEA exposure. Study has identified specific miRNAs, including miR‐22 and miR‐155, as key modulators of pathways associated with ZEA toxicity (Zheng et al., 2019). These miRNAs are implicated in regulating cellular processes such as apoptosis, inflammation, and hormonal signaling, which are perturbed by ZEA.…”
Section: Diagnostic Biomarker Of Regulatory Micrornas During Mycotoxi...mentioning
confidence: 99%